INFLUENCE OF SELECTED FACTORS ON EDUCATIONAL WASTAGE IN PUBLIC SECONDARY SCHOOLS IN MBOONI WEST SUB-COUNTY, MAKUENI COUNTY, KENYA - ANTHONY, ANNE N. (My University, 2019)
The Government of Kenya invests immensely every year in the education sector to provide the appropriate training to its citizens. This is geared towards developing her human capital which is very crucial for nation building. Despite the Government’s high expenditure in financing secondary education, it continues to lose money through wastage in education which manifests through dropouts, repetition and poor academic performance. This connotes internal inefficiency in the education system. The purpose of this study was to investigate the influence of selected factors on educational wastage in public secondary schools in Mbooni West Sub County, Makueni County. The study was guided by the following objectives; to determine the socio-economic factors that influence educational wastage, to establish the influence of student based characteristics on educational wastage, to examine the school based factors that influence educational wastage and to establish the community based factors that influence educational wastage in public secondary schools in Mbooni West Sub County. Descriptive survey design was adopted in the study. The target population was 41 public secondary schools from which 15 schools were selected through stratified random sampling. From the sampled schools 15 principals and 15 academic deans were purposively sampled while simple random sampling was used to select 15 form three class teachers giving a total of 45 respondents. Data was collected using questionnaires and document analysis. Quantitative data was analysed through descriptive statistics using SPSS and presented through tables, graphs, pie charts, frequencies and percentages. Qualitative data was analysed through content analysis. From the study it was established that poor academic performance as a nature of wastage in public secondary schools was high in Mbooni West Sub County, repetition happens more in form four after K.C.S.E as students seek to improve their grades and dropout also existed. The study also established that socio-economic, student based characteristics and community based factors influence educational wastage in public secondary schools in Mbooni West Sub County. Further, the study revealed that school based factors did not influence educational wastage in public secondary schools in Mbooni West Sub County. The researcher recommends that public secondary schools management in Mbooni West Sub County be sensitized on educational wastage to improve efficiency and guidance and counseling to be strengthened to curb wastage.
Keywords: Education